A rare association: inferior vena cava anomalies and congenital heart diseases - İlker Ertuğrul; Vehbi Doğan; Utku Arman Örün; Selmin Karademir (KARE Publishing, 2015)
The numerous variations of abnormalities of the inferior vena cava (IVC) result in anomalies such as isolated left IVC, double IVC and more than 60 types of malformation. These anomalies are rare and recognized incidentally during surgical or radiological procedures. They may lead to clinical complications during abdominal surgery, and predispose to venous thrombosis. Although they have no definite relationship to other congenital cardiac lesions, identification of these anomalies are important for pre-operative planning and post-operative follow-up. This report presents two cases of congenital IVC anomalies accompanied by congenital heart diseases.